Analysis of The Influence of Electronic Wallet Usage, Lifestyle, And Financial Literacy on The Consumptive Behaviour of Generation Z Workers in DKI Jakarta - Ramadhan Putrantona, Farhan; Djunita Pasaribu, Rina (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
This study investigates the influence of electronic wallet usage, lifestyle, and financial literacy on consumptive behavior among Generation Z workers in DKI Jakarta. With a population comprising about one-third of DKI Jakarta's total population, Generation Z is notably technologically adept, often referred to as the Internet or Digital Generation. Employing a quantitative approach, the research utilizes Partial Least Square Structure Equation Modeling (PLS-SEM) and collects data from 407 respondents through an online questionnaire. Findings reveal a positive and significant association between electronic wallet usage and consumptive behavior, as well as lifestyle and consumptive behavior. However, financial literacy exhibits an insignificant and negative impact on consumptive behavior. These insights contribute to understanding the financial behavior of Generation Z workers and may aid in fostering more prudent financial management practices among this demographic.